A geopolitical and geostrategic blueprint for NATO's China challenge. Issue 2 (4th March 2022) - Schreer, Benjamin
Abstract: How will the North Atlantic Treaty Organization (NATO) respond to China's rise? At the heart of NATO's China challenge is the need for allies to grasp the magnitude of Beijing's emerging geopolitical challenge to the Euro-Atlantic area. Utilizing geopolitical theories developed by Halford Mackinder and Nicholas Spykman, the article argues that China is evolving into a transatlantic challenge on the Eurasian "maritime periphery." Consequently, NATO can play a significant role in putting pressure on China's continental direction and its efforts to extend its strategic reach into the "far seas."